The Kosovo memory book as an example of the recording of war victimisation: Methodology and importance for establishing the facts about the past, collective memory and reconciliation - Nikolić-Ristanović Vesna; Radovanović Una; Popović Milica (Temida, 2013)
The aim of this paper is the presentation and analysis of the data collection methodology and content of the first volume of the Kosovo Memory Book 1998-2000, as an example of collecting and displaying data of war victimisation from the territory of the former Yugoslavia. Analysis of the Kosovo Memory Book is done in the context of so far development of methodology of data collection about war casualities, with examination of effects that data presented in the book may have on both victims and restoring of broken relationships among people. First, it provides an overview of the methodology used and data obtained, and then the methodology and data, as well as images of conflicts that established data provide and their consequences are discussed and analyzed. [Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova kreiranja efikasnih mera za njegovo suzbijanje]